أثر العمل في أراضي 1948 على تباين الأجور في الضفة الغربية، فلسطين - جلاد, صلاح (ِAn-Najah National University, 2019)
This Study tried by studying workforce survey by the Palestinian Statistical Breuer System in 2017 in West Bank. The study aims to reach the effect of working in Israel on the daily wage average in short- and long-term period. It is noticed that there are no whole effects for all. But economical one’s studies varied on the effects on education, industry and wages structuring. This study is distinguished to determine the differences between labors in West Bank with those in Israel by measuring the effect of age (experience), revenues from education level ,marital status, economical status, place of residence on the average of wages. A lot of individuals tried to identify wages by reflecting their relation and influence on the individual or organization. The study concluded that wage is the part of economical circle which fulfill the individuals' needs and which is determined by the individual's contribution in the production in addition to to his ability in resorting to demand and need factors built on the market needs based on the purchasing power for the real wage of the worker. The economic model, leaner regression and three equations with small squires (OLS) for special data about work places of West Bank region, West Bank and 1948 lands has been determined by the by the mentioned variables adopted by previous literatures. The results showed positive effects of age, educational levels on wages average for workers in West Bank, while the effect of age of workers inside 1948 lands was less. The results also showed that the wage is more for age mean. For education variable, the more the level, the more the age inside West Bank. The descriptive analysis showed that the effect on females with high levels of education was high; the highest percentage for females with B.A was 54.3%, whereas, the highest for males was for preparatory education was 41.5%. The highest wage for women ranged between 100 and 133 NIS. While, the men wage ranged between 70.1-100 NIS. On the other hand, no effect for education on wages was found for workers inside the 1948 lands. The results revealed the low levels of education among males and the high ones among females in order to occupy a position inside the West Bank which suffers unemployment according to Palestinian Statistical Breuer System. Moreover, the results showed the wage average, according to marital status, was high for married in both West Bank and the Palestinian 1948 lands. The results of economic activities revealed that we are service community; the building sector is the highest in wages, the agricultural one is the neglected despite it is the most important contributor in the economic life. According the governorates compared by Jerusalem governorate wages, Rammalah is the highest whereas Tulkarem is the lowest in the West Bank. Inside the 1948 Lands, workers from Hebron Governorate have the highest wage average, followed by Tulkarem and northern regions; the lowest wages are for Jericho and Ghours.
Keywords: أثر العمل في أراضي 1948 على تباين الأجور في الضفة الغربية، فلسطين